Aplicação de cinza de bagaço de cana-de-açúcar nos atributos químicos e biológicos do solo - Campos, Liliane Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Brazilian potential in the electricity production from the burning of sugar cane bagasse signals to an environmental concern: the large production of residue. The São Paulo industries, especially in areas of ethanol and sugar production, are the largest generators of sugar cane bagasse ash residue. From varied composition, rich in macro and micro nutrients and some toxic metals in a lower concentration, the residue of carbonized biomass has been applied to the soil without any scientific criteria and supported by environmental law. In this sense, the objective of this study was to evaluate the effect of application of sugar cane bagasse ash rates in soil chemical attributes; in soil biological attributes; in humification degree of soil organic matter; and in the carbon (C) and nitrate leaching potential of the soil. For this, the study consisted of four steps: 1) characterization of the ash; 2) incubation experiment with the application of rates of ash equivalent to 0, 5, 10, 20, 40 and 80 ton ha-1 in Oxisols of different textures; 3) field experiment with the application of rates of ash equivalent to 0, 5, 10, 20 and 40 ton ha-1 with and without incorporation into Alfisol under citrus cultivation, being the soil evaluated in three periods: humid and dry in the agricultural year of 2012/2013 and intermediate in the agricultural year of 2013/2014; 4) experiment in columns with the application of rates of ash equivalent to 0, 10, 20, 40 and 80 ton ha-1 in Oxisols of different textures with preserved structure. The designs were: randomized blocks for field experiment and a completely randomized for incubation experiments and in soil columns with preserved structure. In incubation and field experiments were evaluated chemical and biological attributes, total contents of C, nitrogen (N) and the humification degree of organic matter, in addition to functional groups of humic acid fraction in the field experiment for the samples of the ...

O potencial brasileiro na produção de energia elétrica a partir da queima do bagaço de cana-de-açúcar sinaliza para uma preocupação ambiental: a grande produção de resíduos. As indústrias paulistas, especialmente na área de produção de etanol e açúcar, são as maiores geradoras de resíduo da cinza de bagaço de cana-de-açúcar. De composição variada, rica em macro e micro nutrientes e de alguns metais tóxicos em menor concentração, o resíduo da biomassa carbonizada vem sendo aplicado ao solo, sem nenhum critério científico e amparado por lei ambiental. Neste sentido, o objetivo desse trabalho foi avaliar o efeito da aplicação de doses de cinza de bagaço de cana-de-açúcar nos atributos químicos do solo; nos atributos biológicos do solo; no grau de humificação da matéria orgânica do solo; e no potencial de lixiviação de carbono (C) e nitrato do solo. Para isto, o estudo constou de quatro etapas: 1) caracterização da cinza; 2) experimento de incubação, com a aplicação das doses de cinza equivalentes a 0, 5, 10, 20, 40 e 80 t ha-1 em Latossolos de diferentes texturas; 3) experimento de campo, com aplicação das doses de cinza equivalentes a 0, 5, 10, 20 e 40 t ha-1 sem e com incorporação em Argissolo Vermelho Amarelo sob cultivo de citros, sendo o solo avaliado em três períodos: úmido e seco no ano agrícola 2012/2013 e intermediário no ano agrícola de 2013/2014; 4) experimento em colunas com a aplicação das doses de cinza equivalentes a 0, 10, 20, 40 e 80 t ha-1 em Latossolos de diferentes texturas com estrutura preservada. Os delineamentos utilizados foram: blocos casualizados para o experimento de campo e inteiramente casualizados para os experimentos de incubação e em colunas de solo com estrutura preservada. Nos experimentos de incubação e campo foram avaliados os atributos químicos, biológicos, teores totais de C, nitrogênio (N) e o grau de humificação da matéria orgânica ...
Keywords: Solos - Qualidade; Nutrientes; Carbono; Biomassa; Microorganismos; Biomass